Phosphorus uptake and growth of corn with its root system partially exposed to a phosphorus source - Novais, Roberto Ferreira de; Ferreira, Reinaldo Paula; Neves, Júlio César Lima; Barros, Nairam Félix de (Pesquisa Agropecuaria Brasileira, 2014)
To evaluate if the behaviour of corn (Zea mays L.) is affected by the application of a soluble source of phosphorus to only part of its root system, an experiment was carried out under greenhouse conditions, utilizing the split-root technique. One-week old seedlings obtained after germination in vermiculite, were transplanted to geminated pots, each side with 1,4 kg of a Dark-Red Latosol, in such way one-half of the root system was in each pot. Three rates of phosphorus (50, 100 and 200 mg P/kg soil) were applied in one of the two pots or equally divided between them. The P source was well mixed with the soil. Twenty-nine days after transplanting, the plants were harvested (shoots and roots), oven dried, weighted and the plant P content determined. Greater growth and shoot P content were observed when the highest rate of P was equally divided between the two pots of the set compared with its application in only one pot of the set.